KINERJA PEMERINTAH DAERAH PROPINSI BANTEN: PERSPEKTIF PENDAPATAN ASLI DAERAH DAN TEMUAN AUDIT BADAN PEMERIKSA KEUANGAN INDONESIA - Suheri Suheri; Yoyok Cahyono; Dabella Yunia (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This study aimed to examine the influence of local revenues (seen from the number of PAD), and audit findings on the performance of local government. This research was conducted in the District and City of Banten Province. This study used purposive sampling with the amount of data 6 local governments that resulted from the Supreme Audit Agency (BPK), the Department of Revenue and Fiscal Management (DPPKD), and http://otda.kemendagri.go.id. The data in this study were processed using IBM software Statistical Package For Social Science (SPSS) version 20.0. These results indicate that revenue is measured by the amount of revenue does not have an influence on local government performance as measured by performance scores. And audit findings are measured through the number of audit findings (in rupiah) divided by the total budget has no effect on the performance of local government.